2023
DOI: 10.1002/aepp.13344
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at the relationship between concentration, prices, and market power in food retail—A monopolistic competition and differentiated products approach

Abstract: This article examines the determinants and impacts of rising market concentration in food retail. We argue that the differentiated nature of food retail complicates the common assumption that rising market concentration is evidence of growing market power and rising prices. We provide a theoretical explanation for rising market concentration but relatively unchanging market power and prices. We also provide empirical data on prices, gross margins, profit margins, and demand elasticities to support our hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Consumers also tend to fall into multiple segments of shoppers, who vary in the value they place on price, convenience, variety, quality, and other features. Although food retailing concentration has increased in the last 30 years, more in-depth research could examine the competitive impact of increasing concentration (Sexton & Xia, 2018;Dong et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Consumers also tend to fall into multiple segments of shoppers, who vary in the value they place on price, convenience, variety, quality, and other features. Although food retailing concentration has increased in the last 30 years, more in-depth research could examine the competitive impact of increasing concentration (Sexton & Xia, 2018;Dong et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The dataset has been widely used to answer empirical research questions. Related studies have looked at business survival (Choi et al, 2017), entrepreneurship (e.g., Echeverri‐Carroll & Feldman, 2019; Low et al, 2021), healthcare access (Tsui et al, 2020), industrial concentration (e.g., Dong et al, 2023; Rossi‐Hansberg et al, 2021; Zeballos et al, 2023), job creation (e.g., Neumark et al, 2006, 2011), and the local food environment (Berger et al, 2019; Schuetz et al, 2012). Although concerns had been raised by Crane and Decker (2019) about the ability of NETS to detect business trends for some industries, Zeballos and Marchesi (2022) showed that NETS is well suited to capture employment patterns similar to the County Business Patterns (CBP) for the grocery retail industry.…”
Section: Methods and Datamentioning
confidence: 99%
“…Independent grocery retailers are known to offer horizontally and vertically differentiated products and services (Ellickson & Grieco, 2013; Richards et al, 2018; Thomassen et al, 2017). This is often achieved by focusing on serving a particular demographic group, which allows them to establish some degree of local market power and tolerate higher operational costs (Arcidiacono et al, 2020; Çakir et al, 2020; Dong et al, 2023). Ellickson (2007) and Ellickson (2013) find that endogenous fixed costs related to size create an incentive for greater variety at supermarkets, in consistency with the framework in Sutton (1991).…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…According to available information, in 2015, Agricoltori Riuniti Piacentini (A.R.P) merged with Casalasco; in 2017 COPADOR was taken over by Mutti (Tomato News, 2017); and in 2018 Ferrara Foods was purchased by Italtom (Tomato News, 2018), which were some of the main merges since 2014. It must be mentioned that higher level of concentration in the food supply chain does not necessarily mean higher market power or price change (Dong et al., 2023).…”
Section: Concentrationmentioning
confidence: 99%